Comparative Study of Traditional and Improved Containers for Transportation of. Fresh Fish - RAO, C. C. PANDURANGA; KHASIM SAHEB, D IMAM; GUPTA, S S; UNNITHAN, G R; CHARI, S T; SRINIVASAN, R; SANTHANARAJ, T; PILLAI, K V.N (Fishery Technology, 2017)
Traditional bomboo basket and expanded polystyrene insulated plywood box(second band tea-chest) were compared for transportation of iced marine, fresh waterand brackish water fishes from Kakinada to Madras by rail. Quality of fish at despatching and receiving centres was assessed by organoleptic, total volatile nitrogen (TVN) and total bacterial count (TBC) tests. Based on the results obtained and the prices fetched, the traditional bamboo basket apart from being cheaper was found to be as good as expanded polystyrene insulated plywood box for short distance transportation of iced fish involving less than 24 hours journey.